GAMBARAN PROMOSI KESEHATAN DI RUMAH SAKIT MADINA BUKITTINGGI TAHUN 2022 - MERY RAHAYU; ERPIDAWATI ERPIDAWATI; REZI PRIMA (LP2MTBM MAKARIOZ, 2022)
The picture of health promotion in hospitals can be carried out well during the COVID-19 pandemic as well as at Madina Bukittinggi Hospital health promotion is not going well during the COVID-19 pandemic, the measuring indicators are the description of policies, human resources, methods, facilities and infrastructure and budget And Hospital. The purpose of this study is to find out the description of health promotion at the Madina Bukittinggi Hospital in 2022. This research was conducted in June 2022 using a qualitative descriptive method by collecting data using documentation and interviews. The results of this study are that Health Promotion at the Madina Bukittinggi Hospital is running well starting from policies, human resources, methods, facilities and infrastructure and budget funds.